2018
DOI: 10.1111/ggi.13277
|View full text |Cite
|
Sign up to set email alerts
|

Differences among patients with Alzheimer's disease, older adults with mild cognitive impairment and healthy older adults in finger dexterity

Abstract: These results show that declines in finger dexterity can reflect declining cognitive function, and that measurement of finger dexterity using our smart terminal device can facilitate screening of large groups for MCI or AD. Geriatr Gerontol Int 2018; 18: 907-914.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 27 publications
3
54
0
2
Order By: Relevance
“…Three articles discussed the use of new data streams unobtainable from paper-based tests (Dahmen et al, 2017; Fellows et al, 2017; Muller et al, 2017). We also reviewed research that used game performance metrics (Thompson et al, 2012; Tong et al 2016), GPS data (Tung et al, 2014), Virtual Reality activities (Ip et al, 2017; Zygouris et al, 2017), speech changes (Konig et al, 2018), and physical movement changes (Suzumura et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles discussed the use of new data streams unobtainable from paper-based tests (Dahmen et al, 2017; Fellows et al, 2017; Muller et al, 2017). We also reviewed research that used game performance metrics (Thompson et al, 2012; Tong et al 2016), GPS data (Tung et al, 2014), Virtual Reality activities (Ip et al, 2017; Zygouris et al, 2017), speech changes (Konig et al, 2018), and physical movement changes (Suzumura et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The decline in cognitive function is also correlated with changes in physical movement. Suzumura and colleagues (2018) developed a mobile application measuring fine motor skills from tapping on the tablet screen. Participants tapped markers with the left, right, or both hands in time with a rhythm or audio signal.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the rhythmic aspects of inter-hand finger coordination, which is primarily associated with the basal ganglia 24 and corpus callosum, 25,26 was maintained in individuals with early cognitive decline, 27 while a previous study reported that it was reduced in patients with MCI or Alzheimer's disease. 12 Therefore, functional and/or structural changes of frontoparietal regions might be responsible for the reduced bimanual tapping speed and reduced stride length in community-dwelling older people with cognitive decline, whereas functions of the basal ganglia and corpus callosum might still be retained in those individuals.…”
Section: Discussionmentioning
confidence: 99%
“…MCI is characterized by: (i) preserved general cognitive function; (ii) objective memory impairment beyond age; (iii) a lack of dementia; and (iv) little or no impairment of the activities of daily living . Although basic activities of daily living performance is preserved, evidence suggests that subtle changes in motor performance can be found in gait performance, balance function, manual dexterity and dual‐task ability . Furthermore, risk of future cognitive decline is associated with reduced physical function .…”
Section: Introductionmentioning
confidence: 99%
“…Proper execution of motor commands requires accurate sensorimotor integration of somatosensory information [ 57 ]. AD patient’s often have deprivation of sensory-enriching experiences which may affect their health and wellbeing [ 13 , 14 ] and motor abilities, like slowness of movement, altered rhythm, impaired fine motor skills, coordination abnormalities and gait difficulties [ 58 , 59 , 60 ]. Aerobic exercise is likely to provide sensory-enriching inputs and is known to enhance SMI [ 61 ].…”
Section: Discussionmentioning
confidence: 99%